The Relationship Between Age and Working Period with Job Fatigue in Permanent Workers at The Purwodadi Magetan Sugar Factory - Kurniawati, Rizka Triya; Abidin, Zaenal; Marsanti, Avicena Sakufa (Eduvest - Journal of Universal Studies, 2025)
Work fatigue is one of the crucial issues that needs to be addressed because fatigue can cause work skills to disappear, health conditions decrease so that it can trigger work accidents, as well as decreased productivity and work performance. The purpose of this study was to determine the relationship between age and length of service with work fatigue in permanent workers of the Purwodadi Magetan sugar factory. This type of research is quantitative with a cross sectional approach. The sampling technique uses randon sampling, the population in this study were permanent workers at the Purwodadi Magetan Sugar Factory which amounted to 129 workers, the number of samples in this study were 56 respondents. Data analysis test in this study is to use Chi Square. The results of this study indicate that there is a relationship between age and work fatigue with the results of p = 0.042 <0.05, there is a relationship between tenure with work fatigue with the results of p = 0.026 <0.05. Based on the conclusions and suggestions of the research results that there is a significant relationship between age, length of service with fatigue. The suggestion of the research is that Purwodadi Sugar Factory Magetan can make efforts to control fatigue caused by age, length of service.